(3LhGgQ GdcdGes - (3GdfLaj, GdCUagGfj, eMeO MSf Hf HGbQ Hf YHO GdQMje, J (B1266(3g`s
(3ChdgG (B:s
(3GdKGfj ef GdaUhd GdJj JJYdb HGdhVhA hdh HhLg eG cchf GdZGdH ajef CQGOg GdJNdj hfMh Pdc aj CMcGe GdNdhI ef GdhGLH hGdeSJMH hGdecQhg hgj KdGKI GdChd (B...s
(3BNQgG (B:s
... (3HgPG GdebOGQ CjVG Ke Efg EPG cGf jCJj HGdeWdbJjf agj bGFeI ebGe GdeYjfI aeG GdaGFOI aj aYdgG hGMJeGd Jbdjd CaQGO GdeWdb TjA NGd Yf GdaGFOI aJCed LjOG Je GdeLdO GdKGfjs
(3JHUQI GdYfhGf (B:s
(3PcQg GdRQcdj ZdWG HGSe (B( (3LhGgQ GdCMcGe aj TQM TQGFY GdESdGe (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\92s
(3GdPQjYI (B5\1306s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis